(untitled) (Bangladesh Journal of Medical Science, 2026)
Malignant myxoid melanoma histologically presents as atypical spindle cells in a background of dense mucin deposition in connective tissue. It a is a rare variant of malignant melanoma. A substantial overlap in clinical and pathologic features of this variant with other arrays of myxoid containing tumors makes a definitive diagnosis challenging. The myxoid component seen is a response to the tumor cells and therefore is usually seen in metastatic lesions. Though few cases have been reported on skin and face, this case reports the first case of primary myxoid malignant melanoma in the oral cavity. To conclude, proper co-relation of histopathological and immunohistochemical study is the gateway for final diagnosis of myxoid variant of malignant melanoma. Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue 2026, Page : S180-S183